Seasonality Influence on Biochemical and Hematological Indicators of Stress and Growth of Pirarucu (Arapaima gigas), an Amazonian Air-Breathing Fish - Rosiely Felix Bezerra; Maria do Carmo Figueiredo Soares; Athiê Jorge Guerra Santos; Elba Verônica Matoso Maciel Carvalho; Luana Cassandra Breitenbach Barroso Coelho (The Scientific World Journal)
Environmental factors such as seasonal cycles are the main chronic stress cause in fish increasing incidence of disease and mortality and affecting productive performance. Arapaima gigas (pirarucu) is an Amazonian air-breathing and largest freshwater fish with scales in the world. The captivity development of pirarucu is expanding since it can fatten up over 1 kg per month reaching 10 kg body mass in the first year of fattening. This work was conducted in three periods (April to July 2010, August to November 2010, and December 2010 to March 2011) defined according to rainfall and medium temperatures. Seasonality effect analysis was performed on biochemical (lectin activity, lactate dehydrogenase, and alkaline phosphatase activities) and hematological (total count of red blood cells, hematocrit, hemoglobin, and hematimetric Wintrobe indexes) stress indicators, as well as on growth and wellbeing degree expressed by pirarucu condition factor developed in captivity. All biochemical and hematological stress indicators showed seasonal variations. However, the fish growth was allometrically positive; condition factor high values indicated good state of healthiness in cultivation. These results reinforce the robust feature of pirarucu and represent a starting point for understanding stress physiology and environmental changes during cultivation enabling identification and prevention of fish adverse health conditions.